2009
DOI: 10.1089/aid.2008.0170
|View full text |Cite
|
Sign up to set email alerts
|

The Association of HIV Infection with Left Ventricular Mass/Hypertrophy

Abstract: Left ventricular hypertrophy (LVH) is an independent predictor of major cardiovascular events. Cardiovascular risk is increased among human immunodeficiency virus (HIV)-infected patients. To assess LV mass/hypertrophy in HIV infection, 654 women enrolled in the Women's Interagency HIV Study underwent transthoracic echocardiography. There were 454 HIV-infected and 200 uninfected women, mean age 40.8 ± 9.3 years. LV mass/height2.7 was similar between the HIV-infected and the HIV-uninfected groups (41.4 ± 11.1 vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…[17][18][19][20][21][22][23][24] In fact, taken together these studies obtained dissimilar results: if preclinical diastolic dysfunction is often reported, LV mass has been found increased, normal or even reduced and LV systolic function normal or, in few studies, impaired. 38 Actually, these studies can hardly be compared with each other and with our study, mainly because of great differences in such relevant issues as methods employed (that is, clinic BP values, absolute values of LV mass instead of values indexed for body surface area or height ) and patients characteristics (asymptomatic HIV þ patients, HIV þ patients with various degrees of malnutrition, AIDS patients, mixed groups of asymptomatic and symptomatic HIV þ patients, only women, only African or African-American subjects).…”
Section: Left Ventricular Remodelling In Hiv Infection Am Grandi Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23][24] In fact, taken together these studies obtained dissimilar results: if preclinical diastolic dysfunction is often reported, LV mass has been found increased, normal or even reduced and LV systolic function normal or, in few studies, impaired. 38 Actually, these studies can hardly be compared with each other and with our study, mainly because of great differences in such relevant issues as methods employed (that is, clinic BP values, absolute values of LV mass instead of values indexed for body surface area or height ) and patients characteristics (asymptomatic HIV þ patients, HIV þ patients with various degrees of malnutrition, AIDS patients, mixed groups of asymptomatic and symptomatic HIV þ patients, only women, only African or African-American subjects).…”
Section: Left Ventricular Remodelling In Hiv Infection Am Grandi Et Almentioning
confidence: 99%
“…Moreover in some studies HIV þ patients and controls were significantly different with regard to smoking habit, BMI and/or BP values; often no information was available about BP profile or antihypertensive and antidyslipidemic treatment. [17][18][19][20][21][22][23][24] It is beyond the scope of this cross-sectional study to deal with the pathophysiologic mechanisms linking HIV infection and chronic HAART to LV remodelling. However, we can hypothesized that, besides other mechanisms like myocardial viral infection, direct myocardial mitochondrial toxicity by antiviral drugs and chronic inflammation, a relevant role could be played by metabolic complications.…”
Section: Left Ventricular Remodelling In Hiv Infection Am Grandi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…5 In the specific case of LV hypertrophy the data are contradictory, with some authors defending a lower ventricular mass in HIV-infected patients 6 whereas others suggest the opposite. 7,8 LV hypertrophy and LV diastolic dysfunction are related to the development of heart failure in asymptomatic patients and have an important impact on morbidity and mortality in the general population. 9 This might also be the case in persons with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…23 There has been investigation into the relationship between geometry and outcome 24 -26 and studies of the physiology of concentric remodeling, which has been shown to be associated with low-tonormal cardiac output and reduced midwall shortening, markers of subtly impaired systolic function. 27 Similar considerations of geometry have provided insight into LV structure and function in heart failure.…”
Section: Article See P 164mentioning
confidence: 99%